Solve the following equation using the quadratic formula. \( -6 x^{2}=-3 x+14 \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the equation \( -6x^{2} = -3x + 14 \), first, we rearrange it into standard form: \[ -6x^{2} + 3x - 14 = 0. \] Then, multiply through by -1 for simplicity: \[ 6x^{2} - 3x + 14 = 0. \] Now, we can apply the quadratic formula \( x = \frac{-b \pm \sqrt{b^{2}-4ac}}{2a} \), where \( a = 6 \), \( b = -3 \), and \( c = -14 \). Calculating the discriminant: \[ b^{2} - 4ac = (-3)^{2} - 4(6)(-14) = 9 + 336 = 345. \] Now, inserting values into the quadratic formula: \[ x = \frac{-(-3) \pm \sqrt{345}}{2(6)} = \frac{3 \pm \sqrt{345}}{12}. \] Therefore, the solutions are: \[ x = \frac{3 + \sqrt{345}}{12} \quad \text{and} \quad x = \frac{3 - \sqrt{345}}{12}. \]